Action Mechanism of Inhibin α-Subunit on the Development of Sertoli Cells and First Wave of Spermatogenesis in Mice - Cai, Kailai; Hua, Guohua; Ahmad, Sibtain; Liang, Aaixin; Han, Li; Wu, Canjie; Yang, Feifei; Yang, Liguo (PLOS ONE, 2011)
Inhibin is an important marker of Sertoli cell (SC) activity in animals with impaired spermatogenesis. However, the precise relationship between inhibin and SC activity is unknown. To investigate this relationship, we partially silenced both the transcription and translation of the gene for the α-subunit of inhibin, Inha, using recombinant pshRNA vectors developed with RNAi-Ready pSIREN-RetroQ-ZsGreen Vector (Clontech Laboratories, Mountain View, Calif). We found that Inha silencing suppresses the cell-cycle regulators Cyclin D1 and Cyclin E and up-regulates the cell-cycle inhibitor P21 (as detected by Western blot analysis), thereby increasing the number of SCs in the G1 phase of the cell cycle and decreasing the amount in the S-phase of the cell cycle (as detected by flow cytometry). Inha silencing also suppressed Pdgfa, Igf1, and Kitl mRNA levels and up-regulated Tgfbrs, Inhba, Inhbb, Cyp11a1, Dhh, and Tjp1 mRNA levels (as indicated by real-time polymerase chain reaction [PCR] analysis). These findings indicate that Inha has the potential to influence the availability of the ligand inhibin and its antagonist activin in the SC in an autocrine manner and inhibit the progression of SC from G1 to S. It may also participate in the development of the blood–testis barrier, Leydig cells, and spermatogenesis through its effect on Dhh, Tjp1, Kitl, and Pdgfa. Real-time PCR and Western blot analyses of Inha, Inhba, and Inhbb mRNA and Inha levels over time show that Inha plays an important role in the formation of round spermatid during the first wave of spermatogenesis in mice.